Application of Islamic Consumer Theory: An Empirical Analysis in the Context of Bangladesh - Basharat Hossain (Global Review of Islamic Economics and Business, 2014)
One of the main goals of economics is to satisfy the wants of consumer. Like as conventional economics, Islamic economics has also its own law of consumption which is superior to that of conventional economics. This paper presents an empirical survey report on the application of Islamic consumer theory in Bangladesh.The survey is conducted on 184 graduate students of economics from university of Dhaka, Bangladesh. Besides, the consumption framework of Islamic economics has been discussed in this paper. The research finds that, the majority percent of respondents consider Halal (lawful), Haram (unlawful), economic disadvantages of other consumers, scope of reward and punishment in hereafter life (life after death) in their consumptions and other economic activities. The report explores that, though the wants is unlimited, the respondents are capable to control their wants and choose moderate and simple standard of living. In addition, they mentioned that, the use of interest is not essential to run economic activities and interest free economy is possible. It is found that, a large proportion of the respondents did not study Islamic economics due to unavailability of the reading materials in spite of having their interest while half of the respondents read it. Finally, the opinion is found that, religious and ethical instruments (Zakat, donation, hereafter life etc.) should be included in the syllabus of modern economics in school, college and university level. The findings satisfy the assumptions of Islamic consumption framework. Finally, it presents the problems, prospects and recommendations to apply the Islamic consumer theory in Bangladesh.